Hemofilia - Susanto, Michael; Kurniawan, Andree (Fakultas Kedokteran Universitas Pelita Harapan, 2016)
Hemophilia A and B are X-linked recessive diseases that are caused by gene mutations in factors VIII adan IX of the blood clotting cycle. Hemophilia C is an autosomal recessive disease caused by a mutation in factor XI, and acquired hemophilia is largely is an autoimmune process. Hemophilia A and B cannot be distinguished clinically, and severe cases can cause bleeding in the joints and lead to chronic hemophilic arthropathy. The main treatment of hemophilia is infusions of factor VIII and IX, and DDAVP in less severe cases. The main complication that can rise from the use of clotting factors is the appearance of specific inhibitor antibodies that can neutralize the work of the factors. Severe cases of hemophilia A and B by itself carries a poor prognosis, but proper treatment throught the use of clotting factors can give a very good prognosis